1979
DOI: 10.1113/jphysiol.1979.sp012893
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal properties of X and Y cells in the cat lateral geniculate nucleus.

Abstract: SUMMARY1. Extracellular recordings were obtained from units in the dorsal lateral geniculate nucleus of anaesthetized cats.2. Of sixty-nine units, sixty-three could be unambiguously identified as either X (n = 33) or Y (n = 30) by testing the presence of a null response to stationary sine wave gratings presented in different spatial phases.3. In response to stationary gratings flashed on and off, Y cells exhibited bigger, more transient responses than X cells.4. All Y cells but few X cells exhibited a shift ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 29 publications
9
90
1
Order By: Relevance
“…As is well known, V1 receives LGN input from X and Y cells, which themselves carry high-and low-SF input from retina with a ratio of Ϸ3:1 in optimal SF (37,38), which is similar to the ratio observed for our data (Fig. 3).…”
Section: Discussionsupporting
confidence: 79%
“…As is well known, V1 receives LGN input from X and Y cells, which themselves carry high-and low-SF input from retina with a ratio of Ϸ3:1 in optimal SF (37,38), which is similar to the ratio observed for our data (Fig. 3).…”
Section: Discussionsupporting
confidence: 79%
“…LGN cells are sensitive to as high a spatial frequency as area 17 neurons (Derrington and Fuchs, 1979). Furthermore, studies on the guinea pig showed that retinal Y cells respond to the contrastenvelope stimuli (Demb et al, 2001).…”
Section: Organization Of Envelope Processing Pathwaysmentioning
confidence: 99%
“…These include (1) mechanisms within single cells (the time delay between center and surround responses in LGN RFs), (2) mechanisms across a population of cells (the correlation between response latency and RF size reported previously) (Derrington and Fuchs, 1979;So and Shapley, 1979;Sestokas and Lehmkuhle, 1986;Weng et al, 2005), and (3) mechanisms within a network (the time delay between feedforward excitation and feedforward inhibition). For each of these mechanisms, we incrementally vary model parameters and measure SF tuning of the model cortical cells.…”
Section: Relating Coarse-to-fine Dynamics In Lgn and Visual Cortexmentioning
confidence: 99%